Differential Settlement Monitoring System Using Inverse Perspective Mapping - Lim, Hann; Lim, C.; Lim, W.; Yap, H. (Institute of Electrical and Electronics Engineers, 2018)
© 2001-2012 IEEE. Digital measurement of differential settlement is crucial in the structural health assessment. A new differential settlement monitoring system using inverse perspective mapping (IPM) technique is proposed to measure the relative displacement of pillars. First, the displacement of adjacent pillars is indicated by a point of laser beam. Subsequently, camera module attached perpendicularly to the wall captures an image centroid of laser point. As the camera has the image perspective effect, IPM is used to transform the image coordinate of laser point into actual ground plane for vertical displacement measurement in millimeter. A relative displacement graph is plotted onto a Web-base for differential settlement monitoring. The proposed system allows camera to be set up closer to the laser projected wall. Hence, no camera holder is required and no gap is inserted between the camera and targeted screen for laser projection. As a result, the construction of the proposed system is relatively less complex and bulky. A test rig is built to evaluate the proposed differential settlement system. Empirical results showed that the proposed system obtains an accuracy of measurement up to 1 mm ± 0.1 mm. The test results also verify the performance of the system and its applicability to real structures.